EFFORTS TO IMPROVE SCIENCE SKILLS WITH EXPERIMENTAL METHODS AT SPS MERPATI 2 - Rohimah Rohimah; Delina Kasih (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to improve science skills with experimental methods on children aged 5 -6 years at SPS Merpati 2 Jati Murni Bekasi. This research is Classroom Action Research. The research was conducted in two cycles and each cycle was held in two meetings. The subjects of this study were 13 children aged 5-6 years, consisting of 5 boys and 8 girls. Methods of data collection are done through observation and documentation. The data analysis technique was carried out in a qualitative descriptive manner. Increasing science skills is said to be successful if there is an 80% increase in the number of children in science skills from the initial conditions before the action. Children's science skills can be seen from the pre-cycle, cycle I, and cycle II processes. In the pre-cycle, 5 children (38%) had the criteria of not yet developing and 8 children (62%) had the criteria for starting to develop. Then in the cycle, I found 4 children (31%) with the criteria for starting to develop and 9 children (69%) with the criteria for developing according to expectations and in cycle II there were 5 children (38%) developing according to expectations and 8 children (62%) developing very well. So if we look at the percentage per class in children's science skills, we will find that in the pre-cycle process, it was 38.7%, in the first cycle it was 61.5% and in the second cycle it was 85.8%. This proves that the experimental method influences children's science skills.